2018
DOI: 10.18016/ksudobil.407625
|View full text |Cite
|
Sign up to set email alerts
|

Üreticilerin Besi Sığırcılığı Desteklerinden Yararlanması Üzerine Etkili Faktörler

Abstract: Turkey has proper conditions for livestock production but due to the technical and economic problems and also inconsistencies in the agricultural policy, livestock production is not at the desired level. For these reasons, beef cattle farms are adversely affected by free market conditions and face instability in production. In order to reduce this instability, there are several alternative systems to improve the competitiveness and production. Livestock subsidies are one of the most important application of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Livestock enterprises are the main source of raw material for the red meat processing industry. Though Turkey has highly favorable conditions in terms of animal husbandry, structural issues and inconsistencies in policy implementation cause serious problems for livestock enterprises (Ağır & Akbay, 2018;Kayikci et al, 2019). It is essential that these problems are resolved so that the required raw material can be supplied at a reasonable price and consumers can access the food they need at an affordable price.…”
Section: Discussionmentioning
confidence: 99%
“…Livestock enterprises are the main source of raw material for the red meat processing industry. Though Turkey has highly favorable conditions in terms of animal husbandry, structural issues and inconsistencies in policy implementation cause serious problems for livestock enterprises (Ağır & Akbay, 2018;Kayikci et al, 2019). It is essential that these problems are resolved so that the required raw material can be supplied at a reasonable price and consumers can access the food they need at an affordable price.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Abay et al (2017), it was concluded that the education period of the producers positively affected the level of benefits of agricultural supports. In the study conducted by Tan et al (2017), it was determined that there was a positive effect on the benefit of organic farming support, while it had a positive effect on the benefit of beef cattle support in the study conducted by Ağır and Akbay (2018). While it was determined that the number of family members negatively affected the benefit of drip irrigation subsidies, the number of people working in agriculture positively affected the status of utilizing drip irrigation subsidies.…”
Section: Factors Affecting the Benefit From Drip Irrigation Subsidiesmentioning
confidence: 99%
“…Abay et al (2017) determined the situation of the producers benefiting from agricultural subsidies in Turkey, and Tan et al (2017) determined the factors affecting the farmers' benefit from organic farming subsidies. Ağır and Akbay (2018) determined the factors affecting the farmers' benefit from beef cattle subsidies and Doğan et al (2018) determined the factors affecting the level of benefit from young farmer subsidies in Turkey, Beşen et al (2021) determined the status of benefiting from the subsidies of the young farmer project in the TR61 region and Candemir et al (2021) determined the situation of benefiting from drip irrigation support of producers producing grain corn in Kahramanmaraş province.…”
Section: Introductionmentioning
confidence: 99%